Multiple cryosauna sessions for post-exercise recovery of delayed onset muscle soreness (DOMS): a randomized control trial - Wolska, Beata; Domagała, Łukasz; Kisilewicz, Aleksandra; Hassanlouei, Hamidollah; Makar, Piotr; Kawczyński, Adam; Klich, Sebastian (Frontiers in Physiology, 2023)
The main goal was to investigate the effectiveness of cryosauna in preventing the development of delayed onset muscle soreness and to analyze the regenerative changes within muscles after acute fatigue-induced exercises. Thirty-one volunteers were assigned into two groups: 1) an intervention group that participated in cryostimulation after fatigue-induced exercise protocol (CRYO, n = 16) and a control group that performed fatigue-induced exercise protocol, but without any intervention (CONT, n = 15). Main outcome measures include at baseline: blood sample testing (leukocyte content, myoglobin concentration, and creatine kinase activity) and muscle stiffness of lower extremity; immediately after (stiffness), and 24-48-72-96 h post-exercise (blood samples and stiffness). Both groups performed an exercise-induced muscle damage protocol based on repeated countermovement jumps (10 sets, 10 repetitions). The CRYO group underwent a cryosauna (temperature: −110°C, time: 1.5 min per session) intervention during four sessions (i.e., immediately after, 24-48-72 h post-exercise). Leukocyte content was significantly greater 24-48-72 h after exercise in CONT, compared with the CRYO group (p ≤ 0.05 for all), while creatine kinase activity was greater 24-48-96 h in CONT, compared with the CRYO group (p ≤ 0.05 for all). Muscle stiffness increased significantly in rectus femoris, tibialis anterior, and fibula muscle after 48 h post-exercise (p ≤ 0.05 for all), as well as in tibialis anterior and fibula after 72 h post-exercise (p ≤ 0.05 for all) in the CRYO group. Multiple cryosauna was an effective recovery strategy that reduced blood biomarkers and muscle stiffness after exercise-induced muscle damage. Moreover, the development of delayed onset muscle soreness, expressed by a greater muscle stiffness post-exercise, was attenuated to the first 48 h.